Presurgical Evaluation of Epilepsy Using Resting-State MEG Functional Connectivity - Xu, Na; Shan, Wei; Qi, Jing; Wu, Jianping; Wang, Qun (Frontiers in Human Neuroscience, 2021)
Accumulating evidences have shown that epilepsy is an archetypical neural network disorder, which is commonly studied using resting-state functional connectivity irrespective of the presence of epileptiform discharges, and is attracting increasing attention on its contribution to the presurgical evaluation in epilepsy. Among various neuroimaging technologies used to achieve brain functional networks, magnetoencephalography (MEG), with its advantage in high temporal and spatial resolution, is increasingly used to investigate the resting-state functional connectivity in epilepsy. What value does MEG resting-state functional connectivity bring for the epileptic presurgical evaluation? Around this topic, this paper firstly introduced the basic principal of how MEG measures the brain activity and the workflow of constructing the functional connectivity based on MEG signals. And then, it mainly reviewed the evidence of resting-state functional connectivity abnormalities that reveal epileptogenic networks based on low- and high-frequency oscillations, and its added value in combination with intracranial electroencephalography (iEEG). More importantly, this review highlighted that MEG-based resting-state functional connectivity has the potential value to predict post-surgical outcome. And finally, the influence of the eyes-open and eyes-closed conditions on the functional connectivity resting-state are also discussed, which may provide the added value for the epileptic presurgical evaluation.